PENERAPAN MANAJEMEN KELAS OLEH GURU SEKOLAH DALAM PERSPEKTIF TEORI STRUKTURAL FUNGSIONAL - Misharti Misharti; Bambang Wahyu Susanto (Kreatifitas Jurnal Ilmiah Pendidikan Islam, 2021)
Education has an important role in determining the development and self-realization of individuals. Therefore, the teaching and learning process is essentially centered on one issue, namely how teachers implement a classroom management system in an effective teaching and learning process in order to achieve a goal. This study aims to determine the Application of Classroom Management by School Teachers in the Perspective of Structural Functional Theory. The research method used is library research, then analyzed and presented the data findings objectively. The results showed that the application of classroom management in the structural-functional theory was reflected through the role of the group controlled by the classroom teacher. The role of the existing group is expected to meet and satisfy the needs of both teachers and students in the classroom, this will familiarize the needs and interests and bring the expectations of the members closer. Classroom management systems must complement, maintain and improve both individual motivation and the cultural patterns that create and sustain motivation. Keywords: Education, Classroom Management, Structural Functional.